FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PENERIMAAN OPINI GOING CONCERN PADA PERUSAHAAN MANUFAKTUR YANG MENGALAMI FINANCIAL DISTRESS - Ida Ayu Budhananda Munidewi; Nyoman Angga Pradipa (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2019)
Going concern audit opinion is an audit opinion issued by the auditor to ascertain whether the company can maintain its survival or not. The survival of a business entity is influenced by internal constraints, namely constraints within the company itself such as financial conditions, human resources, corporate culture, mastery of technology, internal supervision, etc. and external conditions can be constraints outside the company such as markets, monetary conditions, social, politics and others. Several studies show that the factors that encourage auditors to issue going concern opinions are different and the results are not conclusive. So, this study aims to reexamine the factors that influence the going concern audit opinion. The factors tested in this study are liquidity, audit firm reputation, previous year's audit opinion, and company size. This study uses manufacturing companies that experienced financial distress on the Indonesia Stock Exchange in 2014-2016 as a research sample. The results of purposive sampling, obtained a number of 31 manufacturing companies that meet the sample criteria. Testing the hypothesis in this study using logistic regression analysis. The test results show that only the previous year's audit opinion affected the acceptance of the going-concern audit opinion. Meanwhile, the variable liquidity, KAP reputation, and company size do not affect the acceptance of going-concern audit opinion.